Disability and Shopping : Customers, Markets and the State - Eskyte, Ieva (Abingdon, Oxon : Routledge, 2019)
Disability and Shopping:Customers, Markets and the Stateprovides an examination of the diverse experiences and perspectives of disabled customers, industry and civil society. It discusses how the interaction between the three stakeholders should be shaped at aiming to decrease inequality and marginalisation. Shopping is a part of everyday modern life and yet businesses struggle to adequately meet the needs of 80 million disabled customers in the European Union single market. While there has been extensive research into how individuals engage in customer roles and experience, and how businesses and policies both shape and respond to these, little is known of the same dynamics and practices regarding people with impairments. This book addresses this need by revealing the perspectives, interactions and experiences of disabled customers and their interaction with policy and business. It will be required reading for all scholars and students of disability studies, sociology, marketing and customer relations.
Interaction in the shopInteraction with informal assistants; Interaction with shop assistants; Interaction with 'special' shop assistants; Concluding comments; Bibliography; 5 The lifeworld of accessible markets; Notions of disabled customers and accessibility; International business and civil society's perspectives on disabled customers; National business' perspectives on disabled customers; National civil society's perspectives on disabled customers; International stakeholders' perspectives on accessibility; National stakeholders' perspectives on accessibility; The role of policy discourse
OCLC-licensed vendor bibliographic record.
Keywords: People with disabilities -- European Union countries; People with disabilities -- Services for; Stores, Retail -- Barrier-free design; Shopping -- European Union countries; BUSINESS & ECONOMICS / Commerce; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Sales & Selling / General; SOCIAL SCIENCE / Handicapped; SOCIAL SCIENCE / Social Work; LAW / Disability